Secreted frizzled-related protein 4 and its implications in cancer and apoptosis - Pohl, S.; Scott, R.; Arfuso, Frank; Perumal, V.; Dharmarajan, Arunasalam (Kluwer Academic Publishers, 2015)
Secreted frizzled-related protein 4 (SFRP4) is a glycoprotein that acts as an antagonist of Wnt ligands, causing inhibition of the canonical Wnt signalling pathway. First noticed due to high expression levels during times of increased apoptosis, SFRP4 has been implicated in cell proliferation and differentiation and plays an important role in carcinogenesis. Many tumours such as endometrial, cervical, ovarian, prostate, bladder, colorectal, mesothelioma, pancreatic, renal, and oesophageal tumours are characterised by aberrant promoter hypermethylation, which causes variations in the expression level of SFRP4 when compared to normal cells. Combined experimental data appear to confirm the suggested role of SFRP4 as a local initiator of apoptosis; however, increased SFRP4 expression may not always correlate with an increase in apoptosis, possibly due to the complex interactions between different signalling pathways. SFRP4 can be explored for its use in novel therapeutic modalities as well as being a potential diagnostic biomarker.